2018
DOI: 10.1038/s41380-018-0039-z
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational epigenetic influences of paternal environmental exposures on brain function and predisposition to psychiatric disorders

Abstract: In recent years, striking new evidence has demonstrated non-genetic inheritance of acquired traits associated with parental environmental exposures. In particular, this transgenerational modulation of phenotypic traits is of direct relevance to psychiatric disorders, including depression, post-traumatic stress disorder, and other anxiety disorders. Here we review the recent progress in this field, with an emphasis on acquired traits of psychiatric illnesses transmitted epigenetically via the male lineage. We d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 116 publications
4
75
1
1
Order By: Relevance
“…As reviewed in Ref. , there are data for transgenerational inheritance of diseases/dysfunctions including reproduction, obesity, psychiatric disorders from a variety of environmental stressors including vinclozolin, bisphenol A, atrazine bisphenol A plus phthalates (DEHP and DBP), permethrin plus DEET, methoxychlor, Jet fuel 8, phthalate (DEHP),dioxin, DDT, PCBs, tributyltin, nicotine, alcohol, calorie restriction, high‐fat diets, folate and stress. Mechanisms currently focus on a variety of epigenetic changes including DNA methylation, histone changes and non‐coding RNAs .…”
Section: Transgenerational Inheritancementioning
confidence: 99%
“…As reviewed in Ref. , there are data for transgenerational inheritance of diseases/dysfunctions including reproduction, obesity, psychiatric disorders from a variety of environmental stressors including vinclozolin, bisphenol A, atrazine bisphenol A plus phthalates (DEHP and DBP), permethrin plus DEET, methoxychlor, Jet fuel 8, phthalate (DEHP),dioxin, DDT, PCBs, tributyltin, nicotine, alcohol, calorie restriction, high‐fat diets, folate and stress. Mechanisms currently focus on a variety of epigenetic changes including DNA methylation, histone changes and non‐coding RNAs .…”
Section: Transgenerational Inheritancementioning
confidence: 99%
“…Adverse experiences can have long-lasting transgenerational effects on mental and physical health, and often increase disease risk 4,5 . Traumatic stress in early life in particular, can induce pathologies like psychosis, depression and metabolic dysfunctions in adulthood across generations 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Specific transgenerational benefits of EE exposed fathers have been reported for offspring in rodent models of epilepsy via reduced seizure frequency (Dezsi et al, 2016) and maternal separation, as indicated by a mitigation of anxiety-like behavior (Gapp et al, 2016). Overall, these basic research findings underscore the importance of environmental factors in mediating parental contributions to offspring outcomes through behavioral and potentially epigenetic mechanisms (Yeshurun & Hannan, 2018; described in the next section). This is important to note given that the clinical application of EE in pediatric settings is typically administered by parents (Downs et al, 2018;Morgan et al, 2013Morgan et al, , 2015Purpura et al, 2014;Woo & Leon, 2013;Woo et al, 2015) and not surprisingly, at least for children with autism, therapy is more likely to be beneficial if parents are adherent to the intervention procedures (Aronoff et al, 2016).…”
Section: Harnessing the Environment To Promote Resiliency To Early mentioning
confidence: 77%